Strong Managers and Passive Institutional Investors in the UK - Marc Goergen; Luc Renneboog (Fondazione Eni Enrico Mattei (FEEM), 1999)
The first striking feature is that ownership of the average UK company is diffuse: a coalition of at least eight shareholders is required to reach an absolute majority of voting rights. Even though the average firm has a dispersed ownership, the reader should bear in mind that there are about ten per cent of firms where the founder or his heirs are holding more than 30 per cent. The ownership structure is also shaped by regulation; the mandatory takeover threshold of 30%, for example, has an important impact on the ownership structure. In about 4% of sample companies, corporate shareholders hold just under 30 per cent of the shares. Second, institutional investors are the most important category of shareholders. However, they tend to follow passive strategies and often do not exercise the votes attached to their shares. Third, the passive stance adopted by institutions increases the already significant power of directors, who are the second most important category of shareholders. Franks, Mayer and Renneboog (1998) show that when directors own substantial shareholdings, they use their voting power to entrench their positions and they can impede monitoring actions taken by other shareholders to restructure the board, even in the wake of poor corporate performance. Fourth, there is an important market for share stakes and share stakes do not tend to be dispersed. Fifth, some of the characteristics of the British system of corporate governance, such as the proxy voting and the one-tier board structure, further strengthen the discretionary power of directors. Therefore, the main agency conflict emerging from the diffuse ownership structure is the potential expropriation of shareholders by the management.
Keywords: G32; G34; 330; Corporate governance; Capital and Ownership structure; Corporate Governance; Eigentümerstruktur; Institutioneller Investor; Großbritannien; Aktienstimmrecht